WS2 quantum dots harvesting via sonication assisted liquid exfoliation for the electrochemical sensing of xanthine. (24th August 2022) - Sakthivel, Arunkumar; Chandrasekaran, Anitha; Soosaimanickam, Charlin; Li, Chen-Zhong; Alwarappan, Subbiah
Abstract : WS2 quantum dots (QDs) were prepared by sonication assisted liquid exfoliation in dimethyl formamide (DMF) and dimethyl sulfoxide (DMSO). Abstract : WS2 quantum dots (WS2 QDs) were prepared by sonication assisted liquid exfoliation in dimethyl formamide (DMF) and dimethyl sulfoxide (DMSO). The as-prepared WS2 QDs were characterized by spectroscopic techniques such as UV-visible, photoluminescence and Raman spectroscopy. Further, the crystallinity was identified by XRD and the surface morphology by HR-TEM. WS2 QDs were then utilized as a platform for the electrochemical detection of xanthine and it exhibited a limit of detection and sensitivity of 0.118 μM (S/N = 3) and 7.872 μA cm −2 μM −1, respectively. Further, the proposed sensor was found to be linear in the 1–100 μM range. Hence, it is evident that WS2 QDs can be employed as an electrochemical platform for various sensing and bio-sensing applications.